Biosocial-academic profile and stress in first- and fourth-year nursing students - Leticia Oliveira Bosso; Rodrigo Marques da Silva; Ana Lúcia Siqueira Costa (2017)
To compare the biosocial and academic profile and stress levels between first- and last-year nursing students from a public university in Sao Paulo.This is an analytic and quantitative study. A biosocial and academic form and the instrument for Assessment of Stress in Nursing Students by Costa and Polak were applied to 83 students between February and March 2016.Insufficient income and extracurricular activities contribute to higher levels of stress in both groups of students assessed. Fourth-year students showed higher levels of general stress, particularly generated by the factors: performance of practical activities, professional communication, environment and professional training. Time management produces higher stress in first-year students.Fewbiosocial and academic features equally contribute for the stress levels in first- and last-year nursing students, but those in last-year present higher stress than students who are starting the course.